Macroporous poly(EGDMA-co-HEMA) networks: Morphological characterization from their behaviour in the swelling process - Gomez, Cesar Gerardo (2012)
Polymer beads of ethylene glycol dimethacrylate and 2-hydroxyethyl methacrylate [poly(EGDMA-co- HEMA)] were synthesized by suspension polymerization using different EGDMA contents and stirring speeds. The matrix pore system and the degree of crosslinking are evaluated mainly from the degree of swelling in water, and a mathematical model to describe the network morphology is proposed. The distribution of water into the network was determined from evaporation kinetics of swollen samples, then parameters such as porosity and increase of pore and network volumes were calculated. Networks with a highly stable system of pores were formed when the EGDMA content is higher than 10 mol% for stirring speeds higher than 300 rpm.